2020
DOI: 10.1093/mnras/staa2196
|View full text |Cite
|
Sign up to set email alerts
|

High molecular gas content and star formation rates in local galaxies that host quasars, outflows, and jets

Abstract: We use a sample of powerful z≈0.1 type 2 quasars (‘obscured’; log [LAGN/erg s−1]≳45), which host kiloparsec-scale ionized outflows and jets, to identify possible signatures of AGN feedback on the total molecular gas reservoirs of their host galaxies. Specifically, we present Atacama Pathfinder EXperiment (APEX) observations of the CO(2–1) transition for nine sources and the CO(6–5) for a subset of three. We find that the majority of our sample reside in starburst galaxies (average specific star formation rates… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
82
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(94 citation statements)
references
References 129 publications
12
82
0
Order By: Relevance
“…Since it is known that [O III] often over-predicts the AGN luminosity by about an order of magnitude (Schirmer et al 2013;Hainline et al 2013), this roughly corresponds to a cut of L AGN 10 45 erg s −1 , which can be verified using optical-FIR SED analyses (e.g. Jarvis et al 2019Jarvis et al , 2020. The range of luminosities covered by our sample is designed to be representative of typical AGN luminosities found during the peak epoch of cosmic black hole growth.…”
Section: Our Sample In Contextmentioning
confidence: 90%
See 3 more Smart Citations
“…Since it is known that [O III] often over-predicts the AGN luminosity by about an order of magnitude (Schirmer et al 2013;Hainline et al 2013), this roughly corresponds to a cut of L AGN 10 45 erg s −1 , which can be verified using optical-FIR SED analyses (e.g. Jarvis et al 2019Jarvis et al , 2020. The range of luminosities covered by our sample is designed to be representative of typical AGN luminosities found during the peak epoch of cosmic black hole growth.…”
Section: Our Sample In Contextmentioning
confidence: 90%
“…In Jarvis et al (2020), we studied the CO emission and ultraviolet (UV) -far-infrared (FIR) spectral energy distributions (SEDs) for the nine Quasar Feedback Survey pilot targets. We found that, for at least seven of the targets, the host galaxies had high-molecular gas fractions and short depletion times, which are consistent with those expected for the overall galaxy population with matched stellar masses and specific star formation rates.…”
Section: Pilot Studies Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…As an example, observational signatures of high-velocity and multiphase outflows launched by AGN have been reported in the local and distant Universe (e.g., Cicone et al 2014Cicone et al , 2018Förster Schreiber et al 2014;Feruglio et al 2015;Harrison et al 2015;Jarvis et al 2019;Veilleux et al 2020), and so have pockets of warm and dense gas in AGN hosts (e.g., Weiß et al 2007;van der Werf et al 2010;Mashian et al 2015;Carniani et al 2019). Nevertheless, there is no clear evidence of strong feedback on the cold gaseous and dusty ISM in sizable samples of local galaxies, with AGN hosts showing similar global properties to purely star-forming galaxies (Saintonge et al 2012;Shangguan et al 2020;Jarvis et al 2020;Yesuf & Ho 2020). At high redshifts the situation is more controversial.…”
Section: Introductionmentioning
confidence: 99%